A atenção seletiva como mecanismo neurocognitivo para auxiliar a aprendizagem da noção da função seno por meio das praxeologias matemática e didática - Carvalho, Gabriele Souza de (2023)
This research was designed with the aim of analyzing how a Mathematical and Didactic Organization based on the Anthropological Theory of Didactics for conducting types of tasks can help in manifesting the Selective Attention necessary when learning the notion of the sine function. Thus, the theoretical reference is studies focused on Selective Care with an emphasis on the Characteristics Integration Theory (TIC) and the Anthropological Theory of Didactics (TAD). Regarding the methodological contribution, it was decided to use Classical Didactic Engineering, addressed by Michele Artigue (1996), and of the four phases, only the first two were considered in this research: preliminary analysis; and a priori design and analysis, to answer the following question: how can we encourage the manifestation of Selective Attention necessary to assist in learning the notion of the trigonometric sine function through attentional mechanisms and Mathematical and Didactic Organizations? To this end, in the preliminary analysis, restrictions were identified regarding the epistemological, cognitive and didactic level dimension of the sine trigonometric function, establishing the epistemological obstacles associated with the historical development identified in the history of mathematics, mathematical education and in academic research for later infer them, through a confrontation between historical and learning obstacles. At first, restrictions and/or conditions were also identified regarding teaching the notion of sine function. Thus, the preliminary analysis provided a basis for carrying out the project phase and a priori analysis, a phase in which the elaboration of the Mathematical Organization and Didactic Organization took place, accompanied by three didactic activities, all based on TAD, together with the descriptors of ICT. These organizations were internally validated by mathematics teachers, and it was considered that the organizations have the potential to be used with high school students, aiming to contribute to learning the notion of the sine function, presenting mechanisms to mobilize Selective Attention, among other considerations. present in the text.